How Risky Were Japanese Banks & What Factors Related to The Risks from 2001 to 2008? - Fei, Dawen (2011)
From 2001 to 2008, Japanese banks experienced rescue policies and financial crisis, which was a special period for Japan. This empirical study will address two questions about Japanese banking industry. Firstly it investigates how risky the Japanese banking industry were and then it will found out what factors were likely correlated to the bank risks from 2001 to 2008.